The Use of a Co-Filler Between Silica and Crumb Rubber in Natural Rubber Latex Foam Products - Rattanapan, Suwat; Artchomphoo , Jutatip; Saijun , Diew (Burapha Science Journal, 2026)
This research studied the preparation and mechanical properties of natural rubber latex foam (NRLF) using silica and the mixture of silica with crumb rubber (CRM) as filler. By varying the amount of silica at the levels of 10, 20 and 30 phr, and the ratio between silica and CRM (silica/CRM) at the levels of 0.5/1.0, 0.75/0.75 and 1.0/0.5. From the experiment, it was found that silica can disperse and blend with natural rubber latex well. The mechanical properties, density, depression and compression set of NRLF were studied. The increase in the amount of silica resulted in significant decrease in tensile strength and elongation at break of the NRLF. On the other hand, the higher percentage depression and the percentage of the permanent set after pressing of the NRLF mixed with silica were increased. In the case of using silica and crumb rubber as filler in NRLF, it was found that the characteristics of foaming were uniform. It was found that the tensile strength properties were decreased with decreasing ratio of CRM. With the reduction in the ratio of CRM, the percentage of depression and permanent set were decreased.